Interdisciplinary Text Studies: Structure and Discourse Analysis Approach - Afandi, Akhmad Jazuli (Postgraduate Program, Institut Agama Islam Negeri (IAIN) Kediri, Indonesia, 2023)
The study of text is of paramount importance for the comprehension of scientific disciplines. The principal objective of interdisciplinary text studies is to gain insights into texts from a cross-disciplinary perspective. The analysis of structure and discourse enables the exploration of analytical tools and concepts pertinent to both fields, rendering them applicable to interdisciplinary texts. This research employs qualitative methods and a library approach, utilising structure and discourse analysis. The method of data presentation is both descriptive and analytical. This approach also permits the provision of a comprehensive and perspicacious overview, thereby facilitating a more profound comprehension of the information by the intended audience. The objective of this study is to identify and address shortcomings in the analysis of texts, and to present a range of approaches to this analysis. The analysis of discourse and structure are techniques that can be employed to analyse a range of phenomena, including scientific, social and other phenomena. The efficacy of these techniques is contingent upon the language and text used. The text structure can be elucidated implicitly, textually, or contextually, depending on the requirements of each scientific discipline. The results demonstrate that structure can be a beneficial tool for interdisciplinary text studies and that there is value in paying attention to structural systems, cohesion, and applying syntactic, semantic, and pragmatic study. Additionally, analysing texts about discursive practices and other relevant knowledge can also benefit from discourse analysis.